Endocrine disrupting effects of copper and cadmium in the oocytes of the Antarctic Emerald rockcod Trematomus bernacchii - Chiara Maria Motta; Palma Simoniello; Mariana Di Lorenzo; Vincenzo Migliaccio; Raffaele Panzuto; Emanuela Califano; Gianfranco Santovito (Chemosphere, 2021)
Antarctica has long been considered a continent free from anthropic interference. Unfortunately, recent evidence indicate that metal contamination has gone so far and that its effects are still unknown. For this reason, in the present work, the potential endocrine disrupting effect of two highly polluting metals, copper and cadmium, were examined in the Antarctic teleost Trematomus bernacchii. After a 10 days waterborne exposure, ovarian metal uptake was determined by atomic absorption; in parallel, classical histological approaches were adopted to determine the effects on oocyte morphology, carbohydrate composition and presence and localization of progesterone and estrogen receptors. Results show that both metals induce oocyte degeneration in about one third of the previtellogenic oocytes, no matter the stage of development. In apparently healthy oocytes, changes in cytoplasm, cortical alveoli and/or chorion carbohydrates composition are observed. Cadmium but not copper also induces significant changes in the localization of progesterone and beta-estrogen receptors, a result that well correlates with the observed increase in ovarian metals concentrations. In conclusion, the acute modifications detected are suggestive of a significantly impaired fecundity and of a marked endocrine disrupting effects of copper and cadmium in this teleost species.